איך אתם פותחים -x ^ 2 + 2x-1 = 0?

איך אתם פותחים -x ^ 2 + 2x-1 = 0?
Anonim

תשובה:

x = 1

הסבר:

זה קל!!

# -x ^ 2 + 2x-1 = 0 # { * להשוות ל

# ax ^ 2 + bx + c #

אנחנו מבינים

# a = -1, b = 2, c = -1 #

על ידי פיצול באמצע טווח …. אנחנו מקבלים, PRODUCT =#ca = -1 * -1 = 1 #

SUM =

# 2# *

לכן

# -x ^ 2 + x + x-1 = 0 #

# -x (x-1) + (x-1) = 0 #

# (- x + 1) (x-1) = 0 #

ומכאן

x = 1 …………………………… מקווים לקבל את זה

* דמעות: ד *

תשובה:

# x = 1 #.

הסבר:

משוואה זו ניתנת לפתרון על ידי גורמים.

# -x ^ 2 + 2x - 1 = 0 #

# -1 (x ^ 2 -2x + 1) = 0 #

# x ^ 2 -2x + 1 = 0 #

# x ^ 2 - x - x + 1 = 0 #

#x (x-1) -1 (x-1) = 0 #

# (x-1) (x-1) = 0 #

עכשיו,

# x-1 = 0 #

לכן, # x = 1 #.